Hyaluronic acid modified phosphorus-doped double-copper monatomic nano-enzyme as well as preparation method and application thereof
By using phosphorus-doped double-copper single-atom nanoenzymes and undergoing hyaluronic acid modification in tumor catalytic treatment, the problems of low catalytic efficiency, poor selectivity and insufficient biocompatibility of existing nanoenzymes were solved, and efficient tumor targeting and inhibition effects were achieved.
Patent Information
- Application Number
- CN202411683115.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
Existing nanoenzymes have low catalytic efficiency, poor selectivity and insufficient biocompatibility in tumor catalytic treatment.
Phosphorus-doped double-copper single-atom nanoenzyme (Cu2/PNC) was prepared by solvothermal method, and hyaluronic acid was modified on its surface to prepare Cu2/PNC@HA nanoenzyme. The nanoenzyme improves its catalytic activity and biocompatibility by polymerizing the double copper ion and phosphorus doping material.
The combination of efficient catalytic activity and tumor cell targeting function was achieved, which significantly improved the inhibitory effect on tumor cells and showed high biosafety in the tumor microenvironment.
Smart Images

Figure CN119500199A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials and relates to the preparation of tumor catalytic therapeutic drugs. Background Art
[0002] Nanozymes are nanomaterials with enzyme-like activity, which have high catalytic activity and catalytic stability. In addition, as an inorganic material, nanozymes themselves also have unique physical and chemical properties. Mature nanotechnology can be used to control their size and modify their surface, thereby regulating their catalytic activity. With the continuous development of catalytic science and nanotechnology, there are currently thousands of nanozymes with enzyme-like activity, which can be mainly divided into carbon-based nanozymes, metal-based nanozymes, metal oxide-based nanozymes, metal organic framework-based nanozymes and single-atom nanozymes. Among them, single-atom nanozymes can maximize atom utilization while reducing production costs. Since it was proposed in 2011, it has been a hot research field.
[0003] Despite great efforts in both scientific research and clinical practice, cancer remains one of the world's deadliest diseases. Conventional chemotherapy drugs have low efficacy and serious side effects, which hinder their anti-cancer application. To overcome this limitation, nanozyme therapy strategies have been introduced in treatment to promote the production of toxic substances in tumors without affecting normal tissue cells. This emerging cancer treatment method can be further divided into endogenous stimulation and exogenous stimulation. The former relies on active molecules in tumor tissues and normal tissues (such as H + , H2O2 and glutathione, etc.), resulting in nanozymes producing toxic substances only to the corresponding tumor tissues; while the latter rely on the input of external energy to activate the activated nanozymes in the tumor to catalyze the production of toxic substances in the tumor tissue. Chemodynamic therapy is a typical endogenously stimulated cancer treatment strategy, which uses chemodynamic reagents to convert H2O2 into toxic ROS such as ·OH through Fenton or Fenton-like reactions, inducing cell apoptosis and necrosis.
[0004] By modifying the surface of nanozymes with functional polymers or biomolecules, the functional effects of surface modifiers can be exerted while improving biocompatibility. This is a common method for nanozymes to be applied to tumor catalytic therapy in recent years. Although nanozymes have made great progress, the application of nanozymes in the biomedical field still faces great challenges. For example, compared with natural proteases, most nanozymes have poor dispersibility, poor selectivity, and biocompatibility needs to be improved. For example, the application of publication number CN116673059A discloses a selenium single-atom nanozyme and its preparation method and application, which is composed of nitrogen-doped carbon framework loaded with selenium elements, but its catalytic efficiency is low. Summary of the invention
[0005] In view of the technical problems of low catalytic efficiency and poor selectivity of current nanozymes, the present invention proposes hyaluronic acid-modified phosphorus-doped double copper single-atom nanozymes (Cu2 / PNC@HA) and their preparation methods and applications. The nanozymes prepared by the present invention have maximized atomic utilization and good biocompatibility, laying the foundation for applications in the biomedical field.
[0006] To achieve the above object, the technical solution of the present invention is implemented as follows:
[0007] Cu2 / PNC@HA: First, the ZIF-8 carbon-nitrogen precursor was prepared by solvothermal method; then, the dicopper ions and poly (cyclotriphosphate-4',4'-diaminodiphenyl ether) (PZM) were coated on the surface of ZIF-8 by polymerization; finally, the Cu2 / PNC nanozyme was obtained by pyrolysis. The surface of the Cu2 / PNC nanozyme was coated with hyaluronic acid by electrostatic adsorption to obtain Cu2 / PNC@HA.
[0008] The preparation method of Cu2 / PNC@HA is as follows:
[0009] (1) A methanol solution of 2-methylimidazole and a methanol solution of Zn(NO3)2·6H2O were mixed to obtain solution I, and ZIF-8 (ZIF-8 carbon-nitrogen precursor) was prepared by solvothermal reaction;
[0010] (2) adding a methanol solution of copper acetate monohydrate to a methanol solution of ZIF-8 to obtain solution A; dissolving 4,4'-diaminodiphenyl ether and hexachlorocyclotriphosphazene in methanol to obtain solution B; adding solution A to solution B to obtain solution C;
[0011] (3) adding a mixture of triethylamine and methanol to the solution C prepared in step (2), stirring for reaction, centrifuging, washing and drying to obtain Cu2-PZIF-8;
[0012] (4) The Cu2-PZIF-8 obtained in step (3) is ground and calcined to obtain Cu2 / PNC nanozyme;
[0013] (5) preparing a hyaluronic acid aqueous solution, and then adding the Cu2 / PNC nanozyme aqueous dispersion to obtain solution II, stirring at room temperature, and centrifuging and washing to obtain hyaluronic acid-modified Cu2 / PNC nanozyme (Cu2 / PNC@HA).
[0014] In the above step (1), the volume ratio of the methanol solution of 2-methylimidazole to the methanol solution of Zn(NO3)2·6H2O is (1-4.8):(1-6); the molar ratio of 2-methylimidazole to Zn(NO3)2·6H2O in solution I is (1-12):1; the temperature of the solvent thermal reaction is 20-40°C and the time is 2-4h.
[0015] Furthermore, the solvent thermal reaction further includes centrifugal washing and drying steps.
[0016] In the above step (2), the concentration of the methanol solution of ZIF-8 is 4-20 g / L; the concentration of the methanol solution of copper acetate monohydrate is 2-10 g / L; the volume ratio of the methanol solution of ZIF-8 to the methanol solution of copper acetate monohydrate is (10-50):1.
[0017] In the above step (2), the mass ratio of 4,4'-diaminodiphenyl ether to hexachlorocyclotriphosphazene in solution B is (2-8):(1-4), the concentration of hexachlorocyclotriphosphazene is 0.4-2.7 g / L; the volume ratio of solution A to solution B is (11-51):(30-50).
[0018] In the above step (3), 0.1-0.2 L of triethylamine is added per liter of the mixed solution, and the volume ratio of the mixed solution to solution C is 1:(2.1-3.5); the stirring reaction temperature is 30-50° C. and the time is 3-5 hours.
[0019] Furthermore, the centrifugation conditions in the above steps (1) and (3) are 10000-12000 rpm, and the centrifugation time is 10-20 min; and the drying method is vacuum drying.
[0020] Furthermore, the drying temperature is 50-80°C; and the vacuum degree is 0.08-0.09MPa.
[0021] The calcination conditions in the above step (4) are: heating to 900-1000° C. at a heating rate of 5° C. / min under Ar gas flow, keeping the temperature for 3-4 hours, and cooling to room temperature.
[0022] In the above step (5), the mass ratio of Cu2 / PNC nanozyme to hyaluronic acid in solution II is 1:(1-5); the stirring time at room temperature is 20-24h.
[0023] The centrifugal conditions in the above step (5) are 12000-14000 rpm, and the centrifugal time is 10-20 min.
[0024] Cu2 / PNC@HA was prepared using the above preparation method.
[0025] The above-mentioned Cu2 / PNC@HA is a specific catalytic therapeutic agent for targeting tumor cells or within tumor cells.
[0026] The above-mentioned Cu2 / PNC@HA is used in the preparation of anti-tumor drugs.
[0027] The research of the present invention is divided into three parts: in the first stage, Cu2 / PNC nanozyme was prepared and its physical phase was characterized. The transmission electron microscopy and X-ray powder diffraction results showed that Cu2 / PNC had a dodecahedral structure, a particle size of about 50nm, and an overhanging eaves-like corner structure appeared on the edge. EDS results showed that Cu2 / PNC contained five elements, C, N, O, P and Cu, indicating the successful doping of P element. The single-atom dispersion state of Cu was preliminarily observed by 200kV high-resolution transmission electron microscopy, and the results showed that no nanoparticles or lattice fringes appeared on the carbon-nitrogen carrier. The results of X-ray powder diffraction showed that there were no characteristic peaks of Cu element or its oxide, indicating that there were no copper nanoparticles or nanoclusters in the nanozyme. X-ray photoelectron spectroscopy showed that Cu on the surface of Cu2 / PNC existed in +1 and +2 valences, and there was no 0-valence metal Cu, which further proved the single-atom dispersion state. At the same time, X-ray photoelectron spectroscopy showed that the doping of phosphorus element ensured efficient catalytic active sites. The atomic image of Cu2 / PNC was observed by ac-HAADF-STEM. The image showed that the bright spots existed in pairs, proving the existence of the double copper single atom structure. The POD-like enzyme activity experiment showed that the ability of Cu2 / PNC to catalyze H2O2 to produce ·OH was much higher than that of Cu2 / NC and Cu / NC. In the second stage, Cu2 / PNC@HA was prepared by modifying Cu2 / PNC nanozyme with hyaluronic acid. While enhancing biocompatibility, it can also play a role in targeting tumor cells due to the high expression of CD44 receptors on the surface of tumor cells, which is conducive to the tumor catalytic treatment of Cu2 / PNC. In the third stage, the in vitro anti-tumor effect of Cu2 / PNC@HA was studied. Its inhibitory effect on mouse melanoma B16 cells was investigated by CCK-8 method, proving that Cu2 / PNC@HA has a significant inhibitory effect on the proliferation of tumor cells. Intracellular ROS detection and mitochondrial membrane potential damage studies showed that Cu2 / PNC@HA can catalyze H2O2 in tumor cells to produce reactive oxygen species, leading to a decrease in the mitochondrial membrane potential of tumor cells and inducing apoptosis of tumor cells. The above studies provide theoretical support for tumor catalytic treatment strategies.
[0028] The beneficial effects produced by the present invention are:
[0029] (1) The present invention achieves the combination of efficient catalytic activity and tumor cell targeting function by preparing Cu2 / PNC@HA, and is expected to play a highly efficient therapeutic role in tumor catalytic therapy.
[0030] (2) The present invention first prepares ZIF-8 carbon-nitrogen precursor by solvothermal method, then coats dicopper ions and poly (cyclotriphosphate-4',4'-diaminodiphenyl ether) (PZM) on the surface of ZIF-8 by polymerization, and finally obtains Cu2 / PNC nanozyme by pyrolysis. Hyaluronic acid is coated on the surface of Cu2 / PNC nanozyme to prepare Cu2 / PNC@HA.
[0031] (3) The present invention is the first to dope phosphorus into the double-copper single-atom bionic nanozyme. The double copper simulates the structure of natural multi-copper oxidase. The doped phosphorus atoms have a larger atomic radius and stronger electron donation ability than nitrogen atoms, which can effectively regulate the state density and d-band center of copper atoms, further improving their catalytic activity.
[0032] (4) The present invention prepares Cu2 / PNC@HA for the first time, and a very small amount of copper atoms can exert efficient catalytic activity. The hyaluronic acid is coated on the surface of Cu2 / PNC nanozyme, which greatly improves its biocompatibility. At the same time, the tumor cell targeting function of hyaluronic acid enhances the endocytosis of tumor cells to nanozymes, and better exerts the tumor catalytic therapeutic effect. Moreover, based on the characteristics of low pH and high content of H2O2 (100μM) in the tumor microenvironment, Cu2 / PNC@HA shows the specificity of the tumor microenvironment, which improves the biosafety of Cu2 / PNC nanozyme. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 This is the X-ray powder diffraction pattern of Cu2 / PNC nanozyme.
[0035] Figure 2 This is a high-resolution transmission electron microscopy image of Cu2 / PNC nanozyme.
[0036] Figure 3 EDS elemental energy spectrum observation of elements in Cu2 / PNC nanozyme.
[0037] Figure 4 X-ray photoelectron spectroscopy was used to observe the chemical valence state of Cu in Cu2 / PNC nanozyme.
[0038] Figure 5 The fine spectrum of P in Cu2 / PNC nanozyme was observed by X-ray photoelectron spectroscopy.
[0039] Figure 6 ac-HAADF-STEM observation of the copper double single atom structure in Cu2 / PNC nanozyme.
[0040] Figure 7 Cu2 / PNC nanozyme and its control group catalyzed H2O2 to produce ·OH in in vitro solution.
[0041] Figure 8 To simulate the tumor microenvironment, the toxicity of Cu2 / PNC nanozymes before and after hyaluronic acid modification on B16 cells was detected.
[0042] Fig. 9 To detect the toxicity of Cu2 / PNC nanozyme to B16 cells before and after hyaluronic acid modification under physiological conditions.
[0043] Fig.10 For intracellular ROS detection, nanozymes were observed to catalyze the production of reactive oxygen species from H2O2 in tumor cells. DETAILED DESCRIPTION
[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] The preparation method of Cu2 / PNC@HA in this embodiment comprises the following steps:
[0047] S1. Dissolve 1.9039 g Zn(NO3)2·6H2O in 100 mL methanol and 6.305 g 2-methylimidazole in 80 mL methanol. After complete dissolution, mix the two solutions and stir at 30°C for 3 h.
[0048] S2. The solution obtained in S1 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain ZIF-8;
[0049] S3. Disperse 200 mg ZIF-8 powder into 10 mL methanol and disperse by ultrasonic for 30 min;
[0050] S4. Dissolve 2.5 mg of copper acetate monohydrate in 1 mL of methanol, add it to the solid dispersion obtained in step S3 after complete dissolution by ultrasound, and mix well;
[0051] S5. Dissolve 160 mg of 4,4'-diaminodiphenyl ether and 80 mg of hexachlorocyclotriphosphazene in 50 mL of methanol and dissolve completely by ultrasonication;
[0052] S6. The liquid obtained in step S4 is added to the solution obtained in step S5 and stirred for 10 min;
[0053] S7. Slowly add a mixture of 4 mL of triethylamine and 25 mL of methanol to the solution obtained in step S6, and stir the reaction at 40 ° C for 4 h;
[0054] S8. The solution obtained in S7 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain Cu2-PZIF-8;
[0055] S9. The solid obtained in step S8 was ground into powder, heated to 950°C at a rate of 5°C / min under Ar gas flow, kept for 3h, and cooled to room temperature;
[0056] S10. Disperse 2 mg of Cu2 / PNC nanozyme obtained in step S9 into water, dissolve another 2 mg of hyaluronic acid in water and stir at room temperature for 2 h, then add the Cu2 / PNC nanozyme dispersion dropwise thereto and continue stirring for 24 h;
[0057] S11. The solution obtained in S10 was centrifuged at 13000 rpm for 10 min, washed with H2O three times, and dried under vacuum at 70°C to obtain Cu2 / PNC@HA.
[0058] Example 2
[0059] The preparation method of Cu2 / PNC@HA in this embodiment comprises the following steps:
[0060] S1. Dissolve 1.9039 g Zn(NO3)2·6H2O in 100 mL methanol and 6.305 g 2-methylimidazole in 80 mL methanol. After complete dissolution, mix the two solutions and stir at 30°C for 3 h.
[0061] S2. The solution obtained in S1 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain ZIF-8;
[0062] S3. Disperse 200 mg ZIF-8 powder into 30 mL methanol and disperse by ultrasonic for 30 min;
[0063] S4. Dissolve 2.5 mg of copper acetate monohydrate in 1 mL of methanol, add it to the solid dispersion obtained in step S3 after complete dissolution by ultrasound, and mix well;
[0064] S5. Dissolve 160 mg of 4,4'-diaminodiphenyl ether and 80 mg of hexachlorocyclotriphosphazene in 50 mL of methanol and dissolve completely by ultrasonication;
[0065] S6. The liquid obtained in step S4 is added to the solution obtained in step S5 and stirred for 10 min;
[0066] S7. Slowly add a mixture of 4 mL of triethylamine and 25 mL of methanol to the solution obtained in step S6, and stir the reaction at 40 ° C for 4 h;
[0067] S8. The solution obtained in S7 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain Cu2-PZIF-8;
[0068] S9. The solid obtained in step S8 was ground into powder, heated to 950°C at a rate of 5°C / min under Ar gas flow, kept for 3h, and cooled to room temperature;
[0069] S10. Disperse 2 mg of Cu2 / PNC nanozyme obtained in step S9 into water, dissolve 4 mg of hyaluronic acid in water and stir at room temperature for 2 h, then add the Cu2 / PNC nanozyme dispersion dropwise thereto and continue stirring for 24 h;
[0070] S11. The solution obtained in S10 was centrifuged at 13000 rpm for 10 min, washed with H2O three times, and dried under vacuum at 70°C to obtain Cu2 / PNC@HA.
[0071] Example 3
[0072] The preparation method of Cu2 / PNC@HA in this embodiment comprises the following steps:
[0073] S1. Dissolve 1.9039 g Zn(NO3)2·6H2O in 100 mL methanol and 6.305 g 2-methylimidazole in 80 mL methanol. After complete dissolution, mix the two solutions and stir at 30°C for 3 h.
[0074] S2. The solution obtained in S1 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain ZIF-8;
[0075] S3. Disperse 200 mg ZIF-8 powder into 30 mL methanol and disperse by ultrasonic for 30 min;
[0076] S4. Dissolve 5 mg of copper acetate monohydrate in 1 mL of methanol, add it to the solid dispersion obtained in step S3 after complete dissolution by ultrasound, and mix well;
[0077] S5. Dissolve 160 mg of 4,4'-diaminodiphenyl ether and 80 mg of hexachlorocyclotriphosphazene in 50 mL of methanol and dissolve completely by ultrasonication;
[0078] S6. The liquid obtained in step S4 is added to the solution obtained in step S5 and stirred for 10 min;
[0079] S7. Slowly add a mixture of 4 mL of triethylamine and 25 mL of methanol to the solution obtained in step S6, and stir the reaction at 40 ° C for 4 h;
[0080] S8. The solution obtained in S7 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain Cu2-PZIF-8;
[0081] S9. The solid obtained in step S8 was ground into powder, heated to 950°C at a rate of 5°C / min under Ar gas flow, kept for 3h, and cooled to room temperature;
[0082] S10. Disperse 2 mg of Cu2 / PNC nanozyme obtained in step S9 into water, dissolve another 2 mg of hyaluronic acid in water and stir at room temperature for 2 h, then add the Cu2 / PNC nanozyme dispersion dropwise thereto and continue stirring for 24 h;
[0083] S11. The solution obtained in S10 was centrifuged at 13000 rpm for 10 min, washed with H2O for 3 times, and dried under vacuum at 70°C to obtain Cu2 / PNC@HA;
[0084] Example 4
[0085] The preparation method of Cu2 / PNC@HA in this embodiment comprises the following steps:
[0086] S1. Dissolve 1.165 g Zn(NO3)2·6H2O in 100 mL methanol and 1.232 g 2-methylimidazole in 80 mL methanol. After complete dissolution, mix the two solutions and stir at 30°C for 3 h.
[0087] S2. The solution obtained in S1 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain ZIF-8;
[0088] S3. Disperse 200 mg ZIF-8 powder into 10 mL methanol and disperse by ultrasonic for 30 min;
[0089] S4. Dissolve 2.5 mg of copper acetate monohydrate in 1 mL of methanol, add it to the solid dispersion obtained in step S3 after complete dissolution by ultrasound, and mix well;
[0090] S5. Dissolve 160 mg of 4,4'-diaminodiphenyl ether and 80 mg of hexachlorocyclotriphosphazene in 50 mL of methanol and dissolve completely by ultrasonication;
[0091] S6. The liquid obtained in step S4 is added to the solution obtained in step S5 and stirred for 10 min;
[0092] S7. Slowly add a mixture of 4 mL of triethylamine and 25 mL of methanol to the solution obtained in step S6, and stir the reaction at 40 ° C for 4 h;
[0093] S8. The solution obtained in S7 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain Cu2-PZIF-8;
[0094] S9. The solid obtained in step S8 was ground into powder, heated to 950°C at a rate of 5°C / min under Ar gas flow, kept for 3h, and cooled to room temperature;
[0095] S10. Disperse 2 mg of Cu2 / PNC nanozyme obtained in step S9 into water, dissolve another 2 mg of hyaluronic acid in water and stir at room temperature for 2 h, then add the Cu2 / PNC nanozyme dispersion dropwise thereto and continue stirring for 24 h;
[0096] S11. The solution obtained in S10 was centrifuged at 13000 rpm for 10 min, washed with H2O three times, and dried under vacuum at 70°C to obtain Cu2 / PNC@HA.
[0097] Example 5
[0098] The preparation method of Cu2 / PNC@HA in this embodiment comprises the following steps:
[0099] S1. Dissolve 1.165 g Zn(NO3)2·6H2O in 100 mL methanol and 1.232 g 2-methylimidazole in 80 mL methanol. After complete dissolution, mix the two solutions and stir at 30°C for 3 h.
[0100] S2. The solution obtained in S1 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain ZIF-8;
[0101] S3. Disperse 200 mg ZIF-8 powder into 30 mL methanol and disperse by ultrasonic for 30 min;
[0102] S4. Dissolve 5 mg of copper acetate monohydrate in 1 mL of methanol, add it to the solid dispersion obtained in step S3 after complete dissolution by ultrasound, and mix well;
[0103] S5. Dissolve 160 mg of 4,4'-diaminodiphenyl ether and 80 mg of hexachlorocyclotriphosphazene in 50 mL of methanol and dissolve completely by ultrasonication;
[0104] S6. The liquid obtained in step S4 is added to the solution obtained in step S5 and stirred for 10 min;
[0105] S7. Slowly add a mixture of 4 mL of triethylamine and 25 mL of methanol to the solution obtained in step S6, and stir the reaction at 40 ° C for 4 h;
[0106] S8. The solution obtained in S7 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain Cu2-PZIF-8;
[0107] S9. The solid obtained in step S8 was ground into powder, heated to 950°C at a rate of 5°C / min under Ar gas flow, kept for 3h, and cooled to room temperature;
[0108] S10. Disperse 2 mg of Cu2 / PNC nanozyme obtained in step S9 into water, dissolve 6 mg of hyaluronic acid in water and stir at room temperature for 2 h, then add the Cu2 / PNC nanozyme dispersion dropwise thereto and continue stirring for 24 h;
[0109] S11. The solution obtained in S10 was centrifuged at 14000 rpm for 10 min, washed with H2O three times, and dried in vacuum at 70°C to obtain Cu2 / PNC@HA.
[0110] Example 6
[0111] The preparation method of Cu2 / PNC@HA in this embodiment comprises the following steps:
[0112] S1. Dissolve 1.165 g Zn(NO3)2·6H2O in 100 mL methanol and 1.232 g 2-methylimidazole in 80 mL methanol. After complete dissolution, mix the two solutions and stir at 30°C for 3 h.
[0113] S2. The solution obtained in S1 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain ZIF-8;
[0114] S3. Disperse 200 mg ZIF-8 powder into 30 mL methanol and disperse by ultrasonic for 30 min;
[0115] S4. Dissolve 10 mg of copper acetate monohydrate in 1 mL of methanol, add it to the solid dispersion obtained in step S3 after complete dissolution by ultrasound, and mix well;
[0116] S5. Dissolve 160 mg of 4,4'-diaminodiphenyl ether and 80 mg of hexachlorocyclotriphosphazene in 50 mL of methanol and dissolve completely by ultrasonication;
[0117] S6. The liquid obtained in step S4 is added to the solution obtained in step S5 and stirred for 10 min;
[0118] S7. Slowly add a mixture of 4 mL of triethylamine and 25 mL of methanol to the solution obtained in step S6, and stir the reaction at 40 ° C for 4 h;
[0119] S8. The solution obtained in S7 was centrifuged at 12000 rpm for 10 min, washed with methanol three times, and dried under vacuum at 70°C to obtain Cu2-PZIF-8;
[0120] S9. The solid obtained in step S8 was ground into powder, heated to 950°C at a rate of 5°C / min under Ar gas flow, kept for 3h, and cooled to room temperature;
[0121] S10. Disperse 2 mg of Cu2 / PNC nanozyme obtained in step S9 into water, dissolve another 2 mg of hyaluronic acid in water and stir at room temperature for 2 h, then add the Cu2 / PNC nanozyme dispersion dropwise thereto and continue stirring for 24 h;
[0122] S11. The solution obtained in S10 was centrifuged at 13000 rpm for 10 min, washed with H2O three times, and dried under vacuum at 70°C to obtain Cu2 / PNC@HA.
[0123] Example 7
[0124] The preparation method of Cu2 / PNC@HA in this embodiment comprises the following steps:
[0125] S1. Dissolve 4.47 g Zn(NO3)2·6H2O in 80 mL methanol and 1.232 g 2-methylimidazole in 80 mL methanol. After complete dissolution, mix the two solutions and stir at 40°C for 2 h.
[0126] S2. The solution obtained in S1 was centrifuged at 10000 rpm for 10 min, washed with methanol three times, and dried under vacuum at 80°C to obtain ZIF-8;
[0127] S3. Disperse 200 mg ZIF-8 powder into 50 mL methanol and disperse by ultrasonic for 30 min;
[0128] S4. Dissolve 2 mg of copper acetate monohydrate in 1 mL of methanol, add it to the solid dispersion obtained in step S3 after complete dissolution by ultrasound, and mix well;
[0129] S5. Dissolve 160 mg of 4,4'-diaminodiphenyl ether and 20 mg of hexachlorocyclotriphosphazene in 50 mL of methanol and dissolve completely by ultrasonication;
[0130] S6. The liquid obtained in step S4 is added to the solution obtained in step S5 and stirred for 10 min;
[0131] S7. Slowly add a mixture of 3 mL of triethylamine and 26 mL of methanol to the solution obtained in step S6, and stir the reaction at 30 ° C for 5 h;
[0132] S8. The solution obtained in S7 was centrifuged at 12000 rpm for 10 min, washed with methanol three times, and dried under vacuum at 80°C to obtain Cu2-PZIF-8;
[0133] S9. The solid obtained in step S8 was ground into powder, heated to 1000°C at a rate of 5°C / min under Ar gas flow, kept at this temperature for 3.5h, and cooled to room temperature;
[0134] S10. Disperse 1 mg of Cu2 / PNC nanozyme obtained in step S9 into water, dissolve 5 mg of hyaluronic acid in water and stir at room temperature for 2 h, then add the Cu2 / PNC nanozyme dispersion dropwise thereto and continue stirring for 24 h;
[0135] S11. The solution obtained in S10 was centrifuged at 14000 rpm for 10 min, washed with H2O three times, and dried in vacuum at 70°C to obtain Cu2 / PNC@HA.
[0136] Example 8
[0137] The preparation method of Cu2 / PNC@HA in this embodiment comprises the following steps:
[0138] S1. Dissolve 2.5 g Zn(NO3)2·6H2O in 240 mL methanol and 1.232 g 2-methylimidazole in 50 mL methanol. After complete dissolution, mix the two solutions and stir at 20°C for 4 h.
[0139] S2. The solution obtained in S1 was centrifuged at 11000 rpm for 15 min, washed with methanol three times, and dried under vacuum at 50°C to obtain ZIF-8;
[0140] S3. Disperse 200 mg ZIF-8 powder into 50 mL methanol and disperse by ultrasonic for 30 min;
[0141] S4. Dissolve 2 mg of copper acetate monohydrate in 1 mL of methanol, add it to the solid dispersion obtained in step S3 after complete dissolution by ultrasound, and mix well;
[0142] S5. Dissolve 40 mg of 4,4'-diaminodiphenyl ether and 80 mg of hexachlorocyclotriphosphazene in 30 mL of methanol and dissolve completely by ultrasonication;
[0143] S6. The liquid obtained in step S4 is added to the solution obtained in step S5 and stirred for 10 min;
[0144] S7. Slowly add a mixture of 6 mL of triethylamine and 23 mL of methanol to the solution obtained in step S6, and stir the reaction at 50 ° C for 3 h;
[0145] S8. The solution obtained in S7 was centrifuged at 12000 rpm for 10 min, washed with methanol three times, and dried under vacuum at 80°C to obtain Cu2-PZIF-8;
[0146] S9. The solid obtained in step S8 was ground into powder, heated to 9500°C at a rate of 5°C / min under Ar gas flow, kept at that temperature for 4h, and cooled to room temperature;
[0147] S10. Disperse 1 mg of Cu2 / PNC nanozyme obtained in step S9 into water, dissolve 5 mg of hyaluronic acid in water and stir at room temperature for 2 h, then add the Cu2 / PNC nanozyme dispersion dropwise thereto and continue stirring for 24 h;
[0148] S11. The solution obtained in S10 was centrifuged at 12000 rpm for 20 min, washed with H2O three times, and dried in vacuum at 70°C to obtain Cu2 / PNC@HA.
[0149] Comparative Example 1
[0150] The preparation method of Cu2 / NC@HA in this comparative example comprises the following steps:
[0151] S1. Dissolve 1.9039 g Zn(NO3)2·6H2O in 100 mL methanol and 6.305 g 2-methylimidazole in 80 mL methanol. After complete dissolution, mix the two solutions and stir at 30°C for 3 h.
[0152] S2. The solution obtained in S1 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain ZIF-8;
[0153] S3. Disperse 200 mg ZIF-8 powder into 10 mL methanol and disperse by ultrasonic for 30 min;
[0154] S4. Dissolve 2.5 mg of copper acetate monohydrate in 1 mL of methanol, add it to the solid dispersion obtained in step S3 after complete dissolution by ultrasound, and mix well;
[0155] S5. Slowly add a mixture of 4 mL of triethylamine and 25 mL of methanol to the solution obtained in step S4, and stir the reaction at 40 ° C for 4 h;
[0156] S6. The solution obtained in S5 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain Cu2-ZIF-8;
[0157] S7. The solid obtained in step S6 was ground into powder, heated to 950°C at a rate of 5°C / min under Ar gas flow, kept for 3h, and cooled to room temperature;
[0158] S8. Disperse 2 mg of Cu2 / NC nanozyme obtained in step S7 into water, dissolve another 2 mg of hyaluronic acid in water and stir at room temperature for 2 h, then add the Cu2 / NC nanozyme dispersion dropwise thereto and continue stirring for 24 h;
[0159] S9. The solution obtained in S10 was centrifuged at 13000 rpm for 10 min, washed with H2O for 3 times, and dried under vacuum at 70°C to obtain Cu2 / NC@HA.
[0160] Comparative Example 2
[0161] The preparation method of the Cu / NC nanozyme of this comparative example comprises the following steps:
[0162] S1. Dissolve 1.9039 g Zn(NO3)2·6H2O in 100 mL methanol and 6.305 g 2-methylimidazole in 80 mL methanol. After complete dissolution, mix the two solutions and stir at 30°C for 3 h.
[0163] S2. The solution obtained in S1 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain ZIF-8;
[0164] S3. Disperse 200 mg ZIF-8 powder into 10 mL methanol and disperse by ultrasonic for 30 min;
[0165] S4. Dissolve 2.5 mg of copper nitrate trihydrate in 1 mL of methanol, add it to the solid dispersion obtained in step S3 after complete dissolution by ultrasound, and mix well;
[0166] S5. Slowly add a mixture of 4 mL of triethylamine and 25 mL of methanol to the solution obtained in step S4, and stir the reaction at 40 ° C for 4 h;
[0167] S6. The solution obtained in S5 was centrifuged at 12000 rpm for 20 min, washed with methanol three times, and dried under vacuum at 70°C to obtain Cu-ZIF-8;
[0168] S7. The solid obtained in step S6 was ground into powder, heated to 950°C at a rate of 5°C / min under Ar gas flow, kept for 3h, and cooled to room temperature;
[0169] S8. Disperse 2 mg of Cu / NC nanozyme obtained in step S7 into water, dissolve another 2 mg of hyaluronic acid in water and stir at room temperature for 2 h, then add the Cu / NC nanozyme dispersion dropwise thereto and continue stirring for 24 h;
[0170] S9. The solution obtained in S10 was centrifuged at 13000 rpm for 10 min, washed with H2O for 3 times, and dried under vacuum at 70°C to obtain Cu / NC@HA.
[0171] Implementation effect example 1
[0172] 1. Characterization of Cu2 / PNC Nanozymes
[0173] (1) X-ray powder diffraction observation of the amorphous structural characteristics of single-atom nanozymes
[0174] The nanozyme powder was fully ground and pressed into thin sheets to make its surface smooth and flat. The structure of the sample was measured by Ultima IV X-ray powder diffractometer with Cu Kα radiation source to analyze the crystal structure of the material. The scanning range was 10° to 90° and the scanning speed was 5° / min.
[0175] The results are as follows Figure 1 As shown, Cu2 / PNC nanozyme exhibits amorphous structural characteristics, with an obvious broad shoulder peak at 26° and a less obvious broad shoulder peak at 43°, corresponding to the (002) and (101) planes of graphite carbon. No typical diffraction peaks of Cu (JCPDS: 85-1326) were observed, indicating that there are no Cu particles in the sample, and it is speculated that a very small amount of Cu exists mainly in the form of single atoms.
[0176] (2) High-resolution transmission electron microscopy observation of single-atom dispersion
[0177] The prepared Cu2 / PNC nanozyme was dispersed in ethanol and fully ultrasonicated to make it dispersed evenly. 10 μL of the dispersion was taken with a pipette and dropped on the nickel mesh. The operation was repeated several times to ensure that the nanozyme particles fell on the nickel mesh. The prepared nickel mesh was placed under a Talos F200S 200 kV transmission electron microscope for observation.
[0178] The results are as follows Figure 2 As shown, no nanoparticles or lattice fringes appear in Cu2 / PNC, which further infers that Cu exists in the form of single atoms.
[0179] (3) EDS elemental spectroscopy observation of Cu2 / PNC nanozyme morphology and elements
[0180] The prepared Cu2 / PNC nanozyme was dispersed in ethanol and fully ultrasonicated to make it dispersed evenly. 10 μL of the dispersion was taken with a pipette and dropped on the nickel mesh. The operation was repeated several times to ensure that the nanozyme particles fell on the nickel mesh. The prepared nickel mesh was placed under a Talos F200S 200kV transmission electron microscope for observation. Figure 3As shown, the nanozyme particles present a regular dodecahedral structure, with a particle size distribution of about 50nm, and an overhanging eaves-like corner structure on the edge. The elemental composition and distribution of the nanozyme can also be observed using EDS element distribution. The results show that Cu2 / PNC contains five elements, C, N, O, P and Cu, and the five elements are evenly distributed, which preliminarily proves the successful loading of Cu atoms and the successful doping of P elements.
[0181] (4) X-ray photoelectron spectroscopy to detect the chemical valence state of the nanozyme surface
[0182] The powder sample was tested using an X-ray photoelectron spectrometer, with the radiation source being Al Kα (1486.6 eV). The 284.8 eV of the adsorbed carbon C1s was used as the standard for calibration. According to the peak fitting of the energy spectrum ( Figure 4 ) and found that Cu on the surface of nanozymes mainly exists in the form of +1 and +2 valence, and there is no 0-valent metal state, which ensures the dispersion state of single atoms. At the same time, there is a fine map of P 2p ( Figure 5 ), confirming the existence of element P.
[0183] (5) ac-HAADF-STEM observation of the di-copper atomic structure in Cu2 / PNC nanozyme
[0184] The prepared Cu2 / PNC nanozyme was dispersed in ethanol and fully ultrasonicated to make it dispersed evenly. 10 μL of the dispersion was pipetted and dropped on the gold mesh. The operation was repeated several times to ensure that the nanozyme particles fell on the gold mesh. The prepared gold mesh was placed under a JEM-ARM300F 300 kV transmission electron microscope for ac-HAADF-STEM observation.
[0185] According to the principle of atomic structure imaging, the image contrast is proportional to the square of its atomic number, that is, the larger the atomic number, the higher the image contrast and the brighter the image. Figure 6 As shown, there are a large number of pairs of bright spots on the surface of the nanozyme with a distance of about Cu-Cu distance in copper foil This indicates that Cu exists in the form of twin single atoms.
[0186] (6) POD-like enzyme activity experiments verify that nanozymes catalyze the production of OH by H2O2
[0187] 50 μL of Cu2 / PNC solution with different concentrations (2000, 1000, 500, 250 and 125 μg / mL) was mixed with 50 μL of TMB solution (10 mM) and 400 μL of H2O2 pH 5 NaAc-HAc buffer solution (20 mM), and the mixture was placed on a vortex oscillator for full reaction for 5 min. After centrifugation at 7000 rpm, 100 μL of the supernatant was transferred to a 96-well plate, and the absorbance at 652 nm was measured by a microplate reader to investigate the concentration dependence of the generated ox-TMB. At the same time, the Cu2 / NC and Cu / NC groups were set up for comparison.
[0188] Nanozymes with POD-like activity can catalyze H2O2 to generate hydroxyl radicals (·OH), oxidizing colorless TMB to blue ox-TMB. The amount of ox-TMB produced is quantitatively analyzed by detecting the absorbance of the solution at 652 nm, thereby exploring the POD-like activity of the nanozyme.
[0189] Cu2 / PNC can catalyze H2O2 to generate ·OH, oxidizing colorless TMB to blue (ox-TMB), and the absorbance value at 652nm will increase. Moreover, the ability to generate ox-TMB is stronger under acidic conditions. This experiment explored the POD-like activity of nanozymes under weakly acidic conditions (pH 5). Figure 7 As shown in the figure, with the increase of the concentration of Cu2 / PNC, Cu2 / NC, and Cu / NC nanozymes, the absorbance value of the solution at 652nm continued to increase, indicating that the content of ox-TMB generated by the oxidation of TMB by the catalytic product ·OH continued to increase, and the POD-like activity had a good concentration dependence. Compared with Cu2 / NC and Cu / NC, Cu2 / PNC has the strongest ability to catalyze the generation of ·OH, indicating that its POD-like activity is stronger. Based on the amount of ox-TMB generated by the oxidation of TMB by the catalytic product of nanozymes under the same conditions, the order of the strength of the POD-like activity of nanozymes is: Cu2 / PNC>Cu2 / NC>Cu / NC.
[0190] 2. Antitumor activity of hyaluronic acid-modified Cu2 / PNC nanozymes
[0191] (1) Tumor cell culture
[0192] The mouse melanoma B16 cells used in the experiment were cultured in 1640 medium containing 10% fetal bovine serum at 37°C and 5.0% CO2. In order to compare the inhibitory effect of Cu2 / PNC@HA on B16 cells in physiological environment and tumor microenvironment, the pH of 1640 medium was adjusted to 6.5 with 12mM HCl to simulate the acidic microenvironment of tumor.
[0193] (2) Effect of Cu2 / PNC@HA on tumor cell proliferation
[0194] 8 × 10 tumor cells were cultured in 100 μL of 1640 or DMEM medium. 3 The cells were inoculated at a density of 100 μg / mL in each well of a 96-well plate and cultured overnight at 37°C and 5.0% CO2 to allow the cells to adhere completely. The supernatant was discarded, and Cu2 / PNC@HA with a final concentration of 6.25, 12.5, 25, 50, and 100 μg / mL and H2O2 with a final concentration of 100 μM were added and incubated for 6 h. The absorbance value of each well was measured at 450 nm using the CCK-8 method, and the cell survival rate (A) was evaluated according to the following formula. s : absorbance value of experimental group; A c : absorbance value of control group; A b : absorbance value of blank group).
[0195]
[0196] In the study of the inhibitory effect of Cu2 / PNC@HA and its control group on B16 cells, it was found that the difference between the physiological environment and the tumor microenvironment played a key role in the anti-tumor activity of nanozymes. Figure 8 and 9 As shown in the figure, as the concentration of nanozymes increases, the inhibitory effect on cell growth continues to increase. Moreover, compared with the culture condition of pH 7.4, the cell inhibitory effect of nanozymes is stronger under the culture condition of pH 6.5. This is because under acidic conditions, the catalytic activity of nanozymes is higher, the level of toxic reactive oxygen species produced is higher, and the tumor catalytic therapeutic effect of nanozymes is stronger.
[0197] 3. Intracellular ROS Detection
[0198] B16 cells were cultured at 1×10 5 After inoculation in a 12-well plate and culture for 24 hours, the supernatant was discarded, and different preparations with a final concentration of 25μg / mL and 1640 acidic medium with a final concentration of 100μM H2O2 were added for 6 hours. The supernatant was discarded, washed three times with PBS, and the 2',7'-dichlorofluorodiacetate (DCFH-DA) probe in the ROS detection kit was added and incubated for 30 minutes. PBS was washed three times to remove the probe that did not enter the cells, and then the ROS level in B16 cells was qualitatively analyzed by confocal fluorescence microscopy. At the same time, the control group without drug addition was used as a control. Experimental group settings: Cu / NC@HA, Cu2 / NC@HA, Cu2 / PNC, Cu2 / PNC@HA.
[0199] To further verify the efficiency of Cu2 / PNC@HA in catalyzing ROS production at the cellular level, the level of intracellular ROS production after the action of nanozymes was observed by fluorescence confocal microscopy using a ROS kit (DCFH-DA probe). Intracellular ROS can oxidize non-fluorescent DCFH to generate green fluorescent DCF, and the fluorescence intensity is positively correlated with the ROS content. The green fluorescence in cells treated with Cu2 / PNC and Cu2 / PNC@HA was significantly stronger than that in the control group (Control, Cu / NC@HA and Cu2 / NC@HA) ( Fig.10 ), indicating that the catalytically generated OH and O2 ·- The ROS content is high.
[0200] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a hyaluronic acid-modified phosphorus-doped double copper single-atom nanozyme, characterized in that: Here are the steps: (1) A methanol solution of 2-methylimidazole and a methanol solution of Zn(NO3)2•6H2O were mixed to obtain solution I, and ZIF-8 was prepared by solvothermal reaction; (2) adding a methanol solution of copper acetate monohydrate to a methanol solution of ZIF-8 to obtain solution A; dissolving 4,4'-diaminodiphenyl ether and hexachlorocyclotriphosphazene in methanol to obtain solution B; adding solution A to solution B to obtain solution C; (3) adding a mixture of triethylamine and methanol to the solution C prepared in step (2), stirring for reaction, centrifuging, washing and drying to obtain Cu2-PZIF-8; (4) The Cu2-PZIF-8 obtained in step (3) is ground and calcined to obtain Cu2 / PNC nanozyme; (5) Prepare a hyaluronic acid aqueous solution, then add the Cu2 / PNC nanozyme aqueous dispersion to obtain solution II, stir at room temperature, and centrifuge and wash to obtain the hyaluronic acid-modified phosphorus-doped double copper single-atom nanozyme, namely Cu2 / PNC@HA.
2. The method for preparing the hyaluronic acid-modified phosphorus-doped double copper single-atom nanozyme according to claim 1, characterized in that: The volume ratio of the methanol solution of 2-methylimidazole to the methanol solution of Zn(NO3)2•6H2O in step (1) is (1-4.8):(1-6); the molar ratio of 2-methylimidazole to Zn(NO3)2•6H2O in solution I is (1-12):1; the temperature of the solvent thermal reaction is 20-40°C and the time is 2-4 h.
3. The method for preparing the hyaluronic acid-modified phosphorus-doped double copper single-atom nanozyme according to claim 2, characterized in that: In the step (2), the concentration of the methanol solution of ZIF-8 is 4-20 g / L; the concentration of the methanol solution of copper acetate monohydrate is 2-10 g / L; and the volume ratio of the methanol solution of ZIF-8 to the methanol solution of copper acetate monohydrate is (10-50):
1.
4. The method for preparing the hyaluronic acid-modified phosphorus-doped double copper single-atom nanozyme according to claim 3, characterized in that: In the step (2), the mass ratio of 4,4'-diaminodiphenyl ether to hexachlorocyclotriphosphazene in solution B is (2-8):(1-4), the concentration of hexachlorocyclotriphosphazene is 0.4-2.7 g / L; and the volume ratio of solution A to solution B is (11-51):(30-50).
5. The method for preparing the hyaluronic acid-modified phosphorus-doped double copper single-atom nanozyme according to claim 4, characterized in that: In step (3), 0.1-0.2 L of triethylamine is added per liter of the mixed solution, and the volume ratio of the mixed solution to solution C is 1:(2.1-3.5); the stirring reaction temperature is 30-50°C and the reaction time is 3-5 h.
6. The method for preparing the hyaluronic acid-modified phosphorus-doped double copper single-atom nanozyme according to claim 5, characterized in that: The calcination conditions in step (4) are as follows: heating to 900-1000° C. at a heating rate of 5° C. / min under Ar gas flow, keeping the temperature for 3-4 h, and cooling to room temperature.
7. The method for preparing the hyaluronic acid-modified phosphorus-doped double copper single-atom nanozyme according to claim 6, characterized in that: The mass ratio of Cu2 / PNC nanozyme to hyaluronic acid in solution II of step (5) is 1:(1-5); and the stirring time at room temperature is 20-24 h.
8. A hyaluronic acid-modified phosphorus-doped double copper single-atom nanozyme prepared by the preparation method described in any one of claims 1 to 7.
9. Use of the hyaluronic acid-modified phosphorus-doped double copper single-atom nanozyme according to claim 8 in the preparation of a specific catalytic reagent for targeting tumor cells or within tumor cells.
10. Use of the hyaluronic acid-modified phosphorus-doped double copper single-atom nanozyme according to claim 8 in the preparation of anti-tumor drugs.
Citation Information
Patent Citations
Selenium monatomic nano-enzyme as well as preparation method and application thereof
CN116673059A
Cited By
High-load copper monatomic nano-enzyme as well as preparation method and application thereof
CN119837835A
Double-enzyme active nano-enzyme, preparation method thereof and application of double-enzyme active nano-enzyme in bimodal detection of profenofos
CN121476140A
Bis-enzyme active nanoscale enzyme, preparation method thereof and application thereof in profenofos bimodal detection
CN121476140B